Food quality investigation and control of physicochemical characters of aquaculture shrimp (Litopenaeus Vannamei)- Raw and treated shrimp - SHIMNA. AK; M THANGAVEL (International Journal of Pharma and Bio Sciences, 2018)
The consumer’s acceptance of fishery products depends on several attributes of food quality. As there paucity of information concerning physicochemical differences of untreated Pacific white shrimp, this was taken as the objective for the study. (i) to determine the microbiological quality of freshly caught farm-raised Pacific white shrimp (Litopenaeus vannamei) by determining the aerobic plate count and (ii) to evaluate differences in moisture, pH, Phosphate content shortly after harvest though the proximate composition of shrimp appeared comparable across the farms. Total aerobic count of raw shrimp was twice that of shrimp that were treated with STPP & salt treated shrimp, while shrimp which was only salt treated showed a reduction of a quarter of the density of total aerobic plate count. When raw shrimp was cooked microbial density showed reduction of total plant count by one-tenth. Microbial density was controlled by maintaining high sanitary and hygienic conditions of Food contact and non-food contact surfaces. Total aerobic plate count of Food contact surface (FCS) was maintained at a density less than 55 CFU/ml and Nonfood contact surfaces (NFCS) were maintained at density less than 65 CFU/ml. Though phosphates are the natural components of shrimp, marked change was determined in shrimps treated with STPP while moisture content showed 10% increase which resulted in slight increase in microbial load. However pH did not show a variable change from raw to frozen treated and untreated shrimp even though there was sudden increase in pH at the initial stage of soaking with Sodium Tri Poly Phosphate. Overall, under highly controlled sanitary conditions the microbial loads were within the limits though physicochemical differences after treatment of shrimp with phosphate made a slightly elevated microbial load.